Serous borderline tumor with distant mediastinal metastasis? An Exceptional presentation of ovarian tumor - Julia M. Sołek; Aleksandra Zielińska; Magdalena Sobczak; Urszula Czernek; Robert Kubiak; Radzisław Kordek; Dorota Jesionek-Kupnicka (Polish Journal of Pathology, 2022)
Borderline ovarian tumor is a non-invasive lesion with an excellent prognosis. Here we report a case of 48-year-old woman with distinctive clinical presentation of metastasis of ovarian adenocarcinoma, which was an microinvasive component of a serous borderline tumor. On initial diagnosis patient did not present any clinical manifestation of ovarian tumor. Histological examination of resected ovary showed typical features of the serous borderline tumor with one very diminutive focus of invasive serous adenocarcinoma 4mm in diameter. This exceptional case shows that borderline tumors of ovary with any features of invasion could present an aggressive course with distant metastases.